ANALISIS STRUKTUR MODAL DAN MODAL KERJA PT. INDOFOOD SUKSES MAKMUR Tbk SERTA PENGARUHNYA TERHADAP KINERJA PERUSAHAAN - , (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2023)
Intense competition and uncertain economic conditions make companies have to improve company performance so that they can continue to survive in various business competition situations. One of the efforts to improve the company's performance is by maximizing the factors that influence it. The capital structure and working capital theoretically include factors that affect the company's performance, but need to be analyzed with the aim of knowing the most influential factors as a priority for the company that must be maximized.. The method used in this study is a quantitative method. The data analysis technique used descriptive statistical analysis, classical assumption test, and hypothesis testing. The object of the research is secondary data, namely Financial Statements in the form of Statements of Financial Position and Income Statements for the period 2014-2020. The results of the study show that capital structure partially has a significant negative effect on company performance with the value of Sig. 0.015 < 0.05 and has a tcount of -5.030 > 2.353. Working capital partially has no effect and is not significant to the company's performance with the value of Sig. 0.087 > 0.05 and has a tcount value of 2.509 < 3.182. Meanwhile capital structure and working capital simultaneously have a significant positive effect on company performance with the value of Sig. 0.034 < 0.05 and has a fcount value of 12.658 > 6.94.